Analisis Pengendalian Intern Penerimaan Pajak Bumi Dan Bangunan Pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan - Hafsah Hafsah; Reski Finta Loka (-)
This study aims to determine whether the internal control of land and building tax receipts at the Medan City Regional Tax and Retribution Management Agency has been implemented properly. The author conducted research using descriptive methods. The type of data collected is qualitative data, in which the data sources used are primary data and secondary data and data collection techniques are documentation and interviews with staff of Medan City Regional Tax and Retribution Management Agency in the field of land and building tax. Based on the results of the analysis of this research, it can be seen that the internal control of land and building tax revenue has not been implemented properly because there are still multiple duties on employees and monitoring in collecting taxes has not fully carried out direct monitoring of taxpayers so that many personal or corporate taxpayers are still does not carry out its obligation to pay the PBB. With the inadequate internal control principle, the revenue from land and building tax has not been realized.